ATP and Adenosine in the Retina and Retinal Diseases - Ye, Shan-Shan; Tang, Yong; Song, Jian-Tao (Frontiers in Pharmacology, 2021)
Extracellular ATP and its ultimate degradation product adenosine are potent extracellular signaling molecules that elicit a variety of pathophysiological pathways in retina through the activation of P2 and P1 purinoceptors, respectively. Excessive build-up of extracellular ATP accelerates pathologic responses in retinal diseases, whereas accumulation of adenosine protects retinal cells against degeneration or inflammation. This mini-review focuses on the roles of ATP and adenosine in three types of blinding diseases including age-related macular degeneration (AMD), glaucoma, and diabetic retinopathy (DR). Several agonists and antagonists of ATP receptors and adenosine receptors (ARs) have been developed for the potential treatment of glaucoma, DR and AMD: antagonists of P2X7 receptor (P2X7R) (BBG, MRS2540) prevent ATP-induced neuronal apoptosis in glaucoma, DR, and AMD; A1 receptor (A1R) agonists (INO-8875) lower intraocular pressure in glaucoma; A2A receptor (A2AR) agonists (CGS21680) or antagonists (SCH58261, ZM241385) reduce neuroinflammation in glaucoma, DR, and AMD; A3 receptor (A3R) agonists (2-Cl-lB-MECA, MRS3558) protect retinal ganglion cells (RGCs) from apoptosis in glaucoma.